The Flexibility of Sabbath: Another Pauline Ethnopolitical Device - Noya, Ludwig Beethoven J. (Biblical theology bulletin, 2024)
Sabbath has been considered by scholars to hold great importance in Jewish ethnic identity. However, there are varieties of Sabbath observance among the Jews. This article attempts to view these varieties under the concept of “the flexibility of myth” by Theodorus P. Van Baaren. In acknowledging the flexibility of Sabbath “myth,” this article endeavors to show that such flexibility fits perfectly with Paul’s “ethnic reasoning.” Paul utilizes the flexibility of Sabbath in his ethnic reasoning to maintain his ethnopolitical agenda and claim an authority within the Jewish community of Rome. The article will be divided into four parts. Firstly, the article discusses the flexibility of Sabbath-commandment. Then, it explores the variety of practices of Sabbath observance. Furthermore, the article presents two concepts that are intertwined in Paul’s rhetoric. First is the fluidity of ethnicity and ethnic. Second is the malleability of Paul. Finally, it analyzes Paul’s rhetoric of Sabbath in Romans.